ESG maturity: A software framework for the challenges of ESG data in investment - Cruz, C. (2023)
Given the rising demand for more transparent, consistent, and comprehensive non-financial information in investment, there is a need to provide more reliable, meaningful, and measurable ESG metrics, in a way that most frameworks cannot. Most established frameworks face difficulties and challenges in providing sustainability information to investors in a significant way, lacking in areas such as transparency, reliability, consistency, materiality, and particularly, their focus on the “S” dimension of ESG. The present article purposes to review the challenges associated with several frameworks and to present a solution to overcome them, by giving an overview of a new and innovative software as a service framework, ESG Maturity. This software presents itself as a solution for both reporting companies and their respective investors, by providing both with an assessment of the ESG maturity index of the companies, and delivering a report containing relevant initiatives, strategies, and action plans tailored to each one of them, within different sectors, dimensions, and geographic areas and consequently, their financial and non-financial implementation impact. ESG Maturity is considered a possible answer to the challenges in ESG reporting, having the potential to revolutionize the way companies report their non-financial information and how investors receive it.